The Wagner's law testing in the Visegrád Four countries - Žaneta Tesařová (Review of Economic Perspectives, 2020)
This research paper analyses the relationship between gross domestic product and public expenditures in nominal terms. The analysis is being done by using the standard Peacock-Wiseman specification of the Wagner's law and provides the results for the Visegrád Four countries, i.e. the Czech Republic, Slovakia, Poland and Hungary. We aim to answer a question concerning the existence of a long and/or short-term relationship between the nominal GDP and nominal public expenditures, which consist of current and capital expenditures. To address this question, we employ the VAR model, the Johansen Cointegration test and the VEC model. We study a period between the first quarter of 1999 and the second quarter of 2019 and find out mixed results for the Visegrád Four countries.
Keywords: C32; E60; H50; 330; cointegration; economic growth; GDP; Keynesian hypothesis; public expenditures; Visegrád; Wagner's law